APPLICATION OF THE SCIENTIFIC APPROACH WITH THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL TO INCREASE LEARNING ACTIVITY IN BASIC ACCOUNTING LESSONS FOR CLASS X PS SMK TEKNO SA SURAKARTA ACADEMIC YEAR 2020/2021 - Zuliatun, Nur Arifah (Al'Adzkiya Journal, 2021)
This study aims to increase learning activity by applying a scientific approach with a problem based learning learning model for class X PS SMK Tekno SA Surakarta in the 2020/2021 academic year.This type of research is classroom action research (CAR). This research took place at SMK Tekno SA Surakarta. The subjects in this study were 18 students of class X PS. This research is a classroom action research conducted in 2 cycles. Each cycle is held twice in meetings starting with the action planning stage, the implementation of the action of applying a scientific approach to the Problem Based Learning (PBL) model and reflection. The method of data collection is done by means of observation. Data analysis was carried out by comparing the test results in cycle 1 and cycle 2 with descriptive techniques. This means that the data obtained in this study are presented as they are and then analyzed descriptively to get an overview of the facts and describe them according to the phenomenon. Meanwhile, to measure the increase in student learning using the class average system on the results of the evaluation of each cycle.The conclusion of this study is that there is an increase in student learning activity in the Basic Accounting learning process in class X PS SMK Tekno SA Surakarta in the 2020/2021 academic year by applying a scientific approach with a problem based learning (PBL) learning model from 16 students to 18 students.